'Dead before morning': How Beckett's 'Petit Sot' Never Got Properly Born. Issue 2 (September 2015) - Pilling, John
Abstract : An analysis of how and why, after having been appropriately presented, annotated and set as per the publisher's requests in respect of the annotated edition of the Faber/Grove Collected Poems of Samuel Beckett, 'Appendix Two' had to be jettisoned, notwithstanding the editors' reluctance to comply with an obligation imposed on them by those who control the copyrights.